Compressed‐sensing accelerated magnetic resonance imaging of inner ear. Issue 9 (4th August 2021) - Jiang, Yuan; Wang, Xiaoying; Zhu, Lina; Liu, Jing; Zhang, Xiaodong; Hu, Xiaoyu; Lin, Zhiyong; Wang, Ke; Qin, Naishan
Abstract: Objective: To compare conventional method and compressed‐sensing (CS) accelerated 3D balanced fast field echo imaging (bFFE) of inner ear. Methods: Twenty patients with suspected inner ear disease underwent CS accelerated 3D‐bFFE (CS‐bFFE) and conventional 3D‐bFFE (Con‐bFFE) by a 3T MRI. The overall image quality, motion artifacts, and image quality of specific structures of inner ear were assessed on ordinal scales by three radiologists who were blinded to the scan protocols. Kendall W test was used to evaluate interobserver agreement and Wilcoxon test was performed to compare the image quality and motion artifacts between CS‐bFFE and Con‐bFFE. Results: The acquisition duration of CS‐bFFE (1 min 53 s) was 49% faster than Con‐bFFE. Three radiologists had good inter‐observer agreement of image quality ( Kendall W value of 0.829 for CS‐bFFE and 0.815 for Con‐bFFE) and motion artifacts evaluation ( Kendall W value of 0861 for CS‐bFFE and 0.707 for Con‐bFFE). The better overall image quality of CS‐bFFE was assessed (4.93 ± 0.23 for CS‐bFFE, 4.53 ± 0.70 for Con‐bFFE, Z = −2.254, p  = 0.024). The image quality score of facial and cochlear nerve gained higher in CS‐bFFE (4.93 ± 0.23 for CS‐bFFE, 4.58 ± 0.64 for Con‐bFFE, Z = −2.094, p  = 0.036). No significant difference of motion artifacts ( p  = 0.050) between CS‐bFFE and Con‐bFFE. Conclusions: The CS‐bFFE improves image quality and reduces acquisition time significantly, and it is a feasible MRI protocol for inner ear imaging.